A multi-dimensional approach to the financial inclusion in EU countries - Teodora Cristina Barbu; Iustina Alina Boitan; Sorin Iulian Cioaca; Carmen Obreja (Revista română de economie, 2017)
The topic of financial inclusion has gained increased attention, on the background of international frameworks and policies devoted to inclusive societies, inclusive financial systems, sustainable and inclusive growth. However, existing literature and practice lack a generally accepted, reliable and easy to interpret quantitative measure of financial inclusion. The novelty of our paper relies on developing a financial inclusion index, comprising an updated set of indicators which account for current developments of the financial industry and the continuous diversification and complementarity of financial products people have access to. It is the first study comprising all the 28 EU countries and covering a large, recent time horizon (2008-2013). The index has been computed for each year considered and a ranking has been provided to comparatively assess the evolution of a given country on the financial inclusion scale. Our findings revealed that one-third of EU countries show moderate financial inclusion, while the remaining ones depict low financial inclusion, with different degrees of severity. A constant presence at the bottom limit of financial inclusion, in each of the six years, has been Romania. This result reflects a reality, namely the lack of official concern from authorities and financial institutions in respect of monitoring, measuring and stimulating financial inclusion. We believe that the index proposed in this paper could act not only for assessing the degree of inclusion at a given moment of time, but also as a tool for monitoring and signaling the imperative involvement of regulators, financial institutions and civil society in designing and implementing policies and programs for enhancing inclusive financial products.
2665773-9; 2344-4657; Revista română de economie; 717197875